Prevalence of Zinc Deficiency in Obese Adults with Increased Appetite in Shiraz, Iran - Zare 1, Narjes; Eftekhari 1,2*, Mohammad Hassan; Ghaem 3, Haleh; Dashtabi 1, Arash (Shahroud Journal of Medical Sciences, 2019)
Background: Low serum zinc concentration is associated with obesity,and its deficiency has been linked to many pathogenesis aspects of obesity. The present study was designed to evaluate the prevalence of zinc deficiency in the obese adults with increased appetite in Shiraz,Fars province, south of Iran. Furthermore, we aimed to evaluate the serum zinc correlation with some demographic and anthropometric indices. Methods: In this study, 260 adults with the ages ranged from 25 to 55 years old were selected for serum zinc concentration. Age, sex, job, education level, physical actively, weight, height, body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist to hip ratio (WHR) were also recorded for each participants. Using calorimeter method, we considered the serum level of zinc less than 70µg/dL as deficient. Results: Mean serum level of zinc was 96.37 ± 18.24 µg/dL. The prevalence rate of zinc deficiency was 8%, which was more prevalent among female participants than male ones with no significant difference (9.8% and 4.6%, respectively, Pvalue = 0.14). The participants’ characteristics were not statistically different between normal and deficient groups, and serum zinc concentration had no correlation with age, sex, height, weight, BMI, WC, HC, and WHR. Conclusions: Zinc deficiency in obese adults living in Shiraz is as prevalent as other population groups, and also other regions of Iran. Zinc deficiency is considered as a possible risk factor for obesityrelated diseases, and requires more investigations. Keywords: Zinc, Deficiency, Prevalence, Obesity, Iran.